Structural, paleogeographic and topographic evolution of the northern Tibetan Plateau margin: Evidence from the southern Tarim basin, northern Hexi Corridor, and Qaidam basin - Ritts, Bradley D; Bovet, Paul M; Kent-Corson, Malinda L; Darby, Brian J; Hourigan, Jeremy; Zhuang, Guangsheng; Graham, Stephan A; Yue, Yongjun (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1309 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.121-122